2017
DOI: 10.4067/s0718-95162017000400003
|View full text |Cite
|
Sign up to set email alerts
|

Strawberry monocropping: Impacts on fruit yield and soil microorganisms

Abstract: The objective of this work was to explore the impacts of intensive strawberry monocropping during five years on the fruit-yield and on the microbial soil activity and composition. Field trials were performed in two plots: P1(a soil with five years of consecutive strawberry cropping), and P2 (a soil with just one year of strawberry cropping). Fruit-yield was quantified; total microorganisms and four functional groups (cellulolytics, nitrogen-fixers, phosphate solubilizers, and siderophores producers) were quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Similar problem is widespread in other crops such as apple, cucumber, strawberry, and potato 4 , 5 . In ecology, such negative plant-soil feedback is viewed as a type of Janzen–Connell effect 6 .…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Similar problem is widespread in other crops such as apple, cucumber, strawberry, and potato 4 , 5 . In ecology, such negative plant-soil feedback is viewed as a type of Janzen–Connell effect 6 .…”
Section: Introductionmentioning
confidence: 83%
“…For example, phosphatase helps to mineralize organic P, which responds to changes in soil management 19 . Decline in soil enzyme activities have been observed for crops after continuous cropping including strawberry, cucumber, potato, cotton, and Sanqi, partly due to the altered soil properties and microbial communities 5,22,[36][37][38] . For instance, Sun et al 22 showed that the activities of phosphatase and urease in the soil decreased 69 and 92% after 3 year of continuous cropping of Sanqi.…”
Section: Principal Component and Pearson Correlation Analyses Of 13 Smentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that using a biological product for a longer period of time would have a stronger effect on the physical properties of the samples, especially those made on a peat base and prepared for use in greenhouses. This is even more true because, over time, the microbial biomass and activity in the soil decrease [50]. Other scientists claim that due to the use of biological products and other biostimulators, the amount of organic carbon in the soil increases [20,22].…”
Section: Effect Of Biotreatment On Soil and Substrate Density Total P...mentioning
confidence: 99%
“…Sufficient organic matter increased the soil quality and microbial population that is necessary for long term strawberry production (Medeiros et al, 2015;Lovaisa et al, 2017). Soil organic matters support the proliferation of heterotrophic microbes in soil and their function in macronutrient nutrient cycle (Hoorman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%